Penyelesaian CCVRPTW Menggunakan Biased Random Key Genetic Algorithm-Populasi Degradasi - Christiana, Listy Avri; Prasetyo, Hari (Jurnal Ilmiah Teknik Industri, 2017)
The article presents the Biased Random Key Genetic Algorithm-Population Degradation (BRKGA-PD) design for completing Capacitated Closed Vehicle Routing Problem with Time Windows (CCVRPTW) on soft drink distributions that have been studied by Sembiring (2008). The goal is to determine some closed routes in meeting consumer demand with time limits and limit the capacity of vehicles used, so the total cost of distribution is minimal. The proposed algorithm adopts the extinction of population size. BRKGA-PD is coded using Matlab programming with the best parameter setting. The resulting solution is a subrute with a minimum of distribution fee. This algorithm is compared with two other methods, namely BRKGA general and heuristic methods. The results of this study can be concluded that the BRKGA-PD method is able to improve the general BRKGA because with a time difference that is not significant can provide cost savings of Rp. 6.857,- and BRKGA-PD is better than heuristic method because it can save more cost Rp. 87.000,-.